3 SMK Bukit Rangin students create Therapaint, an art therapy innovation to help students’ mental health, wins gold at CITREX UMPSA 2025 - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 3 July 2025 – Concerned with the declining mental health among students, three students from Sekolah Menengah Kebangsaan (SMK) Bukit Rangin, Kuantan, Putri Siti Nurshahira Balqis Shazriyana Noriman, Rabiatul Firzanah Rosman, and Aienin Suraya Shahril Abdul Hakim, have introduced an art therapy-based innovation titled Therapaint.